PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN MELALUI VARIABEL INTERVENING KOMITMEN ORGANISASI PADA CV. AUTO 99 MALANG - Budiarti, Tatik; Bukhori, Mochamad (LP2M Institut Teknologi dan Bisnis Asia Malang, 2017)
This study aims to determine the effect of variable of organizational culture on employee performance, variable organizational commitment to employee performance and organizational culture variables on the performance of employees through the organization's commitment to CV AUTO 99 Malang. This type of research is Eksplanatory Research, the research method is quantitative. The population in this study amounted to 57 employees. The total sample of 57 employees using the technique of saturated samples (Path). Anailsis deskiptif This study uses quantitative and statistical analysis used to determine the direct and indirect relationships between the variables of organizational culture, organizational commitment variable and variable employee performance. The results obtained organizational culture variables directly affect organizational commitment and also directly affects the performance of employees. Organizational commitment directly affects the performance of employees and organizational culture are also indirect effect on employee performance through organizational commitment to the CV. AUTO 99 Malang.